2020
DOI: 10.12659/msm.922703
|View full text |Cite
|
Sign up to set email alerts
|

TNNC1 Reduced Gemcitabine Sensitivity of Nonsmall-Cell Lung Cancer by Increasing Autophagy

Abstract: Background As we know, chemotherapy resistance is a critical factor leading to recurrence and metastasis of nonsmall-cell lung cancer (NSCLC). To clarify the key target and potential mechanism of resistance to gemcitabine (GEM) in NSCLC, we selected Gene Expression Omnibus Data Set and statistically analyzed a parent cell group and a GEM-resistant cell group. Results showed that the expression of troponin C1, slow skeletal and cardiac type (TNNC1) in GEM-resistant cells was higher than in parent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Through cytoskeleton reorganization, overexpression of TNNC1 regulated epithelial cancer cell motility [30]. Besides, TNNC1 was reported as an oncogenic gene in non-small-cell lung cancer [31] and ovarian cancer [32]. In this study, we for the first time revealed the oncogenic role of TNNC1 in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Through cytoskeleton reorganization, overexpression of TNNC1 regulated epithelial cancer cell motility [30]. Besides, TNNC1 was reported as an oncogenic gene in non-small-cell lung cancer [31] and ovarian cancer [32]. In this study, we for the first time revealed the oncogenic role of TNNC1 in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 65%
“…Besides, troponin genes were reported to be aberrant expressed in various cancer cells, and play roles as oncogenic or anti-tumor mediator [12]. For the selected examples, TNNC1 was found to be highly expressed in nonsmall-cell lung cancer cells and it was able to reduce chemotherapy resistance [31]. Inhibition of TNNC1 expression was effective in controlling the metastasis of ovarian cancer [32].…”
Section: Introductionmentioning
confidence: 99%
“…(Sanches et al., 2019) Restoring blood flow through pharmacological or mechanical intervention is the key for treating ischaemic injury. (Ye et al., 2020) However, reperfusion can lead to severe secondary injury, known as, cerebral ischaemia‐reperfusion (CIR) injury. (Doyle et al., 2008) There is an urgent need to find more effective drugs to reduce brain injury and improve brain function in patients with CIR.…”
Section: Introductionmentioning
confidence: 99%
“…CX3CR1 [441], S100A12 [442], PF4 [443], MPO (myeloperoxidase) [444], WNT7A [445], SLC6A4 [446], BDNF (brain derived neurotrophic factor) [447], CXCL10 [448], NEK7 [449], CYP1B1 [450], ABCA3 [451], TRIB3 [452], PCSK9 [453], FGF2 [454], ACKR4 [455], FASN (fatty acid synthase) [456], VIP (vasoactive intestinal peptide) [457], KL (klotho) [458], BMPR2 [459], APOA1 [323], TLR3 [460], CCR2 [461], TLR7 [462], CAV1 [463], WWC2 [464], TFPI (tissue factor pathway inhibitor) [465], EPAS1 [466] and CCDC40 [467] could serve as a potential therapeutic for pulmonary hypertension treatment. A previous study reported that the genes include CX3CR1 [468], CSF2 [469], CLDN18 [470], TRIM58 [471], PF4 [472], FFAR2 [473], MPO (myeloperoxidase) [474], CD5L [475], SH3GL2 [476], ITGA2B [477], S100A8 [478], VEGFD (vascular endothelial growth factor D) [479], CXCL11 [480], IL1A [481], WNT7A [482], SSTR1 [483], AQP4 [484], SCD (stearoyl-CoA desaturase) [485], SLC6A4 [486], BDNF (brain derived neurotrophic factor) [487], CXCL10 [488], ODAM (odontogenic, ameloblast associated) [489], CASP5 [490], CCL8 [491], TMEM100 [492], S100A9 [493], IL1B [494], CXCR1 [495], CXCR2 [496], WNT3A [497], BMI1 [498], CYP1B1 [499], FCN3 [500], TTN (titin) [501], SHISA3 [502], AZGP1 [503], ABCA3 [504], CD36 [505], EDNRB (endothelin receptor type B) [506], BTNL9 507], CEBPA (CCAAT enhancer binding protein alpha) [508], TRIB3 [509], TNNC1 [510], PCSK9 […”
Section: Discussionmentioning
confidence: 99%